TINJAUAN HISTORIS ILMU HADIS - Khabib Sharifudin (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2024)
Hadith science is a discipline that studies hadith, both narrators, sanad, and everything related to hadith. Hadith is the second source of law after the Qur'an. Hadith is defined as everything that is based on the Prophet Muhammad, be it actions, words, or provisions. This article will discuss the history of the development and codification of hadith science from the time of the prophethood to the tabi'tabi'in. The method used by the author in writing this article is the library research method by collecting data in the form of journals, books, and other documents related to hadith. Historically, hadith was only written down in the 2nd century AH.